Prediction markets for economic forecasting - Erik Snowberg; Justin Wolfers; Eric Zitzewitz (Center for Economic Studies and ifo Institute (CESifo), 2012)
Prediction markets - markets used to forecast future events - have been used to accurately forecast the outcome of political contests, sporting events, and, occasionally, economic outcomes. This chapter summarizes the latest research on prediction markets in order to further their utilization by economic forecasters. We show that prediction markets have a number of attractive features: they quickly incorporate new information, are largely efficient, and impervious to manipulation. Moreover, markets generally exhibit lower statistical errors than professional forecasters and polls. Finally, we show how markets can be used to both uncover the economic model behind forecasts, as well as test existing economic models.
Keywords: C50; G14; 330; prediction markets; forecasting; Wirtschaftsprognose; Prognoseverfahren; Börsenspiel; Theorie